The relationship between the uses of land and the network of movement and roads (study area, Najaf city) (Journal of Planner and Development, 2008)
The interaction in the city is reflected in the movement of people motivated by their activities and their economic and social goals, which include many variables subject to the planning process in the interpretation of this movement and the mapping of trends of transport intensity through the concept of transport function and its functional relationships with the uses of the earth in the sustainability and effectiveness of the movement of transport and Economic activity and population movement. Transport planners are concerned with the requirements of land use, which are linked to and included in the transport planning process as a factor for the future transport needs. There is a strong relationship between the transport system and the land use system. Any change in patterns The movement is followed by a change in land uses, and these new uses will generate new passage. It is therefore possible to identify the research problem of the importance of the definition of the joints of functional correlation between the uses of different land and the impact (and impact at the same time), on the network of roads within and outside the city. As a conclusion, it is possible to say that the concentration and high density of traffic is confined to the main centers of the city and continues in the adjacent areas, which are characterized by the predominance of the use of a single function often on them, gradually leading to the loss of dominance of that use and balance with residential use and the needs of its uses such as services Educational, recreational and financial.